2013
DOI: 10.1016/j.labeco.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Employment sector and pay gaps: Genetic and environmental influences

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…The response rate for the latest survey was 77%, totaling 12,502 twin pairs. The attrition and representativeness of the twin sample have been documented previously (e.g., Kaprio et al, 1979;Maczulskij, 2013). Our analysis focuses on twin pairs for whom we have data on alcohol consumption, other covariates and disability pension.…”
Section: Data Sources and The Samplementioning
confidence: 98%
“…The response rate for the latest survey was 77%, totaling 12,502 twin pairs. The attrition and representativeness of the twin sample have been documented previously (e.g., Kaprio et al, 1979;Maczulskij, 2013). Our analysis focuses on twin pairs for whom we have data on alcohol consumption, other covariates and disability pension.…”
Section: Data Sources and The Samplementioning
confidence: 98%
“…Importantly for our purposes, all three twin surveys contained information on alcohol consumption. Similarly to, for example, Hyytinen et al (2013) and Maczulskij (2013), the twin data are linked to FLEED using personal identifiers. There are no misreported ID codes, which implies very good match.…”
Section: Data Sources and The Samplementioning
confidence: 99%
“…Hyytinen et al, 2013;Maczulskij, 2013). Prior studies can be consulted for details about the response rates, attrition and representativeness of the twin sample (Kaprio et al, 1979; see also Hyytinen et al, 2013;Maczulskij, 2013). Hyytinen et al (2013, p. 63) and Maczulskij (2013, p. 95) provided evidence for the representativeness of the twin sample by comparing it to a one-third random sample of all Finns using FLEED and covering the same age cohorts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The twin study contains information on smoking, alcohol use, symptoms of illnesses and reported diseases, medication use, physical characteristics, psychosocial factors and multi-faceted information on experiences at work and in one's personal life. Based on previous explorations, our twin data are a representative sample of the general population in Finland (Kaprio et al, 1979;Maczulskij, 2013a;Hyytinen et al, 2013). The linked data remain representative also for the smaller sample of MZ twins (Maczulskij, 2013b, p. 124-125).…”
Section: Datamentioning
confidence: 93%